PENYULUHAN TENTANG KESIAPSIAGAAN IBU HAMIL DALAM MENGHADAPI BENCANA GEMPA BUMI - Ruri Maiseptya Sari I; Dewi Aprilia Ningsih; Metha Fahriani; Suhita Tri Oklaini (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2021)
Background: The main cause that resulted in the emergence of many victims due to the earthquake disaster was the lack of knowledge of community preparedness about disasters and the lack of community preparedness in anticipating the disaster. Purpose: This Community Service aims to increase knowledge about the preparedness of pregnant women in dealing with the earthquake and tsunami disaster in the work area of the Pasar Ikan Health Center in Bengkulu City. Methods: This activity was carried out by distributing leaflets, conducting counseling and evaluating activities, the implementation of this activity was carried out in the work area of the Bengkulu City Fish Market Health Center from November 25 to November 28, 2021 with a total of 24 pregnant women participating. Results: In the implementation of the activities that we carried out, there was an increase in the knowledge of pregnant women after the Preparedness education was carried out in the event of an earthquake and Tsunami. Where the average before the counseling was done was 45 percent, it increased to 80 percent after the counseling was done. In addition, pregnant women also seemed enthusiastic during the counseling session, this can be seen from the response of pregnant women in the question and answer session Conclusion: From the results of this service activity, there was an increase in knowledge of pregnant women about preparedness during disasters, especially earthquakes and tsunamis.